Interpreting the use of video media in mathematics learning at SMPN Satap 1 Bajawa - Hari, Christina Lusiana; Bela, Maria Editha; Lola, Teofania Kristina; Wea, Marselina (Desimal: Jurnal Matematika, 2025)
Mathematics learning, particularly at the junior secondary level, is often perceived as abstract and difficult, which can reduce students’ motivation and engagement. One instructional strategy that has the potential to address this issue is the use of YouTube-based instructional video media. This study aims to describe teachers’ and students’ interpretations of the use of video media in mathematics learning at SMP Negeri Satap 1 Bajawa, as well as to identify the challenges encountered during its implementation. The study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with mathematics teachers and students, and documentation of learning activities. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the use of YouTube-based video media positively influences the learning process by increasing students’ motivation, focus, and conceptual understanding of mathematical material. Students perceived video-based learning as more interesting and enjoyable compared to conventional instruction, and they appreciated the ability to replay learning content independently. Teachers reported that video media supported clearer explanations of abstract concepts and improved student engagement. However, several challenges were identified, including limited availability of supporting facilities and the pace of explanations in some videos, which were considered too fast for certain students. Overall, the study concludes that YouTube-based instructional video media have strong potential to support more meaningful and contextual mathematics learning, particularly in schools with limited resources, provided that the content and implementation are adapted to students’ learning needs..